2007
DOI: 10.1007/s00122-007-0673-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of a new cytoplasmic male sterility system (hau) in Brassica juncea and its transfer to B. napus

Abstract: A novel cytoplasmic male sterility (CMS) was identified in Brassica juncea, named as hau CMS (00-6-102A). Subsequently, the male sterility was transferred to B. napus by interspecific hybridization. The hau CMS has stable male sterility. Flowers on the A line are absolutely male sterile, and seeds harvested from the line following pollinations with the maintainer gave rise to 100% sterile progeny. The anthers in CMS plants are replaced by thickened petal-like structures and pollen grains were not detected. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
2
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 36 publications
1
34
2
4
Order By: Relevance
“…Although it has relatively high similarity with orf263 in alloplasmic male sterile Brassica tournefortii at the nucleotide level, the restorer lines for tour CMS systems were found to be ineffective for restoring fertility in the hau CMS line. This may suggest that they were different from each other [22]. A comparative analysis of the mitochondrial genome of the hau CMS line and its maintainer line further confirmed that orf288 was CMS-associated gene in hau CMS line in B. juncea .…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Although it has relatively high similarity with orf263 in alloplasmic male sterile Brassica tournefortii at the nucleotide level, the restorer lines for tour CMS systems were found to be ineffective for restoring fertility in the hau CMS line. This may suggest that they were different from each other [22]. A comparative analysis of the mitochondrial genome of the hau CMS line and its maintainer line further confirmed that orf288 was CMS-associated gene in hau CMS line in B. juncea .…”
Section: Discussionmentioning
confidence: 92%
“…A cultivar trilocular line, J163-4, in B. juncea with fertility anther was also used as control in our study [39]. The anthers in the hau CMS plants are replaced by thickened petal-like structures and the sterility of the hau CMS initiates at the stamen primordium polarization stage [22]. Seeds from the hau CMS line, its iso–nuclear maintainer line and the normal type line “J163-4” were harvested in an experimental field at Huazhong Agricultural University in 2011.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Xiangyu (Liu et al 2005) and hau in B. juncea (Wan et al 2008). Maintainer and restorer lines of 681A CMS are the same as those for pol , but 681A lines differ from pol lines in their mitochondrial genome organization, suggesting that 681A might be a variant of pol CMS.…”
Section: Origins Of Cms and Male Sterility-inducing Mitochondrial Genesmentioning
confidence: 99%
“…Maintainer and restorer lines of 681A CMS are the same as those for pol , but 681A lines differ from pol lines in their mitochondrial genome organization, suggesting that 681A might be a variant of pol CMS. On the other hand, restorers for hau cytoplasm have not been identified so far and pol or nap restorers fail to rescue hau -induced male sterility (Wan et al 2008). …”
Section: Origins Of Cms and Male Sterility-inducing Mitochondrial Genesmentioning
confidence: 99%